Study of the Relationship Pattern of Ecdysis with the Age of Crayfish Type Procambarus clarkii Aged 21 Days - Intan Fatimah Rahmania (Contributions of Central Research Institute for Agriculture, 2021)
The purpose of this study was to determine the pattern of LAT ecdysis, especially the Freshwater Lobster Procambarus clarkii, aged 21 days to 66 days. In crustaceans, moulting is part of the growth mechanism. Changes in shape and size can only occur if the hard calcareous exoskeleton is removed before the new cuticles have hardened. Periodic moulting or ecdysis continues by separating the old cuticle from the new instar, this growth process takes place continuously. The moulting cycle can be divided into four stages, namely: proecdysis, ecdysis, metecdysis and intermoult. Moulting occurs when the LAT is 2 to 3 weeks old. Death often occurs in this period, death occurs due to cannibalism caused by moulting in LAT which does not take place simultaneously because each individual grows differently, thus allowing cannibalism to occur in other individuals who are molting. Process moulting in LAT may be standardized by administering the hormone Phytoecdysteroids given at the time of proecdysis. To find out proecdysis, you must first know the LAT ecdysis pattern. The results showed that the more often the LAT had molted, the longer the number of days needed for the LAT to experience the next moulting. This is because the size of the lobster is getting bigger so that energy is needed not only for activity and maintenance but also for growth.